Sweden : 2006 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Sweden. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This 2006 Article IV Consultation highlights that a broad-based economic upturn is under way in Sweden, spurred by strong global growth and supportive fiscal and monetary policies. Private consumption has served as the engine of expansion, supported by resurgence in investment and buoyant exports. The momentum of the current recovery is expected to continue, although to ease back in 2007-08 in the face of capacity constraints and fading policy stimulus. Growth is also expected to ease back in 2007-08.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet